Religion traditionnelle et gestion durable des ressources floristiques en Côte d'Ivoire : Le cas des Ehotilé, riverains du Parc National des Îles Ehotilé - François Malan Djah (VertigO)
Ehotilé Islands emerge from the Aby lagoon, in the South-east Côte d'Ivoire. There were established to National Park on the Ehotilé people’s initiative, supported by their traditional religion demonstrations. In a perspective of a co-management of this park, a first analysis of social and cultural foundation contributing to the conservation of natural resources is taking place. Thus, this work is a part of an ethnobotanical survey led in four Ehotilé villages. It shows that some aspects of Ehotilé religion (the function of Komian, the worship of Nyango and the sacred sites) have a perceptible impact on the conservation of plant resources. Despite the changes due to social pressures, this religion is still alive among Ehotilé people, and in our view, cannot be glossed over in the implementation of a policy of co-management of the Ehotilé Island National Park.